The Florida Bull Test 2012–2013 - Graham Cliff Lamb; Nicolas DiLorenzo (EDIS, 2013)
The North Florida Research and Education Center in Marianna, Florida annually hosts the Florida Bull Test. By controlling the environmental factors and taking Expected Progeny Differences (EPD’s) into account, the data clearly emphasizes the dual importance of genetics and environment in all cattle types. This 9-page fact sheet presents the procedures, rules, and results of the 2012-2013 test. Written by G. Cliff Lamb and Nicolas DiLorenzo, and published by the UF Department of Animal Sciences, October 2013. http://edis.ifas.ufl.edu/an290